Phase field crystal study of nano-crack growth and branch in materials. (31st May 2016) - Yingjun, Gao; Zhirong, Luo; Lilin, Huang; Hong, Mao; Chuanggao, Huang; Kui, Lin
Abstract: The phase field crystal (PFC) method is a new multiscale method, which can reproduce physical phenomena on an atomic level and on a diffusion time scale for the microstructure evolution of materials. The morphology of microcrack propagation and the branch of single crystal materials under tensile strain with a fixed grip condition are simulated by using PFC coupling with an external field method. The results show that microcrack propagation depends a lot on the applied strain. The crack starts to grow and branch when the strain reaches a critical value for biaxial tension. The temperature parameter may also have an effect on crack propagation and the branch. In order to indicate the connection between the PFC results and materials behavior, the energy balance approach is used to analyze the mechanism of crack extension, and also the critical value of the strain for crack extension is obtained. The simulated results are in good agreement with other simulation results and experimental results.